Species diversity of plankton as an indicator of water quality at sewerage disposal of several Industries In Surakarta . - WIRYANTO WIRYANTO; ARI SUSILOWATI; AHMAD DWI SETYAWAN (Biodiversitas Journal of Biological Diversity, 2003)
The objective sof the research were to study the physical, chemist and biological (plankton) conditions of sewerage disposal from several lndustries In Surakarta, Physical parametert observed were temperature, total soluble solid and the texture of soli sediment, chemistry parameters observed were, includll"l,g,DO, pH and EC, while blotlo parameters observed were density and diversity of plankton, The research was elane, betvleen July and September 2002 at sewerage disposal of ten Industries InS urakarta. Sample collected at 0, 100 16I'1Q 200m irespectlvely from the waste reseuree, Temperature data measured for both water and sediment resulted ,that the average, temper'ature of ten industries was >26Â°0, with certain Industry clearly dissolved Its high temperatur,e wU,QIi1 its uwer:ag;e., The iSS varies betvleen Industries, depend on the speclfloatlon of the Industry, pH detegteGw,as '1>1, :an;'ct tile 00, data. mee_suredwere relatively high due to aeration process. Based on the plankton diversity indices :aUwater !se;weysg,e, from tlhe ten Industries were oategorlzed as heavy polluted,@ 2003 Jurusan 9101091 FMIPA UNS SurakartaKata kuncl: sewerage, plankton, Surakarta